Aerobic fitness in young soccer players: The Yo-Yo intermittent endurance test as indicator of aerobic power and anaerobic threshold - Valamatos, M. J.; Charrua, C.; Gomes-Perreira, J.; Mil-Homens Santos, P. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
It has been demonstrated that soccer performance requires well-developed aerobic and anaerobic fitness. Consequently, the assessment of the VO2max and anaerobic threshold is important for monitoring the effectiveness of the physical training program of the soccer players. These aerobic fitness measurements are accurately evaluated using a variety of laboratory protocols during treadmill continuous running until exhaustion. However, the soccer performance is characterized by an intermittent and highintensity physical effort. Therefore, it seems logical to evaluate the athletes` capacity with sport-specific endurance tests. For this reason, some field tests have been proposed as practical and specific alternatives to laboratory assessments. One of the most popular is the Yo-yo Intermittent Endurance Test Level 2 (YIET-2), suggested by Bangsbo (1994) for well-trained subjects. The purpose of this study was to analyse the YIET-2 as indicator of aerobic power and anaerobic threshold in youth soccer players. Methods: Physiological responses were determined in eighteen welltrained elite young soccer players (age = 17.4 + 0,5 years old; body mass = 71.7 + 7.4 kg) while performing the Yoyo Intermittent Endurance Test (YIET) and a Progressive continuous Running Treadmill Test (PRTT) until exhaustion. Maximal heart rates (HRmax), respiratory exchange ratio (RER), O2 pulse, maximal ventilation (VEmax), oxygen uptake (VO2 ), and expired carbon dioxide (VCO2 ) were measured. Expired gases in both conditions were analyzed using a portable lightweight breath-by-breath gas analyzer (K4b2; Cosmed, Rome, Italy). The Ventilatory Threshold (VT) was detected by V-slope method. Paired-Samples T Test was used to determine if there were significant differences in the physiological responses in the PRTT and YIET. Correlation coefficients were used to determine the relationship in the performances and selected physiological measures between tests. Results: Results showed that VO2max, HRmax, RER, O2 pulse, and VEmax were not significantly different between PRTT and YIET performance (p<0.05). There were a positive correlations in the measured VO2max in both PRTT and YIET (p<0.01). However, there no significant correlations between players` performance in the YIET (i.e. number of completed shuttles or total distance covered) and the measured VO2max in both laboratory and in field conditions. In contrast, there were strong significant correlations between the same YIET performance and the ventilatory threshold measured in PRTT (p<0.01). These findings show that YIET and PRTT elicit similar cardio respiratory responses. However, the players` performance in the YIET seems to be a weak indicator of aerobic power in youth well trained soccer players. Probably, the YIET can be considered an aerobic-anaerobic soccer-specific field test, and can be regarded as a good indicator of aerobic capacity.